Pengaruh Pengetahuan Produk dan Literasi Digitalisasi Terhadap Minat Transaksi Siswa SMK Tritech Informatika di Bank Syariah - Sinurat, Yuni Sulistiawati (Al-Sharf: Jurnal Ekonomi Islam, 2023)
The purpose of this study is to determine the influence of product knowledge, digitalization literacy and the transaction interest of SMK Tritech Informatics students at Sharia Banks. This research uses quantitative if research methodology, the data used are primary data. Data analysis techniques with descriptive tests, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests. Theauthors are 60 students of SMK Tritech Informatika vocational Islamic banking who study Islamic banking through digital services in the form of product knowledge and digitalization literacy. The data processing process uses the SPSS program version 26.0. The result of this study is that the Product Knowledge variable (X1) has no effect on transaction interest seen from t table (0.4621.673) and the significant level is greater than 0.05 (0.646 0.05). The variable of Digitalization Literacy (X2) has an effect on transaction interest as seen from the tt table (3.1061.673) and its significance which is smaller than 0.05 (0.003 0.05. On the influence of product knowledge, Digitalization Literacy, affects transaction interest. The influence of product knowledge at SMK Tritech Informatika is 0.328 or 32.8%.